Impact of perfusion on neuronal development in human derived neuronal networks - Donatella Di Lisa; Andrea Andolfi; Giacomo Masi; Giuseppe Uras; Pier Francesco Ferrari; Sergio Martinoia; Laura Pastorino (APL Bioengineering)
Advanced in vitro models of the brain have evolved in recent years from traditional two-dimensional (2D) ones, based on rodent derived cells, to three-dimensional (3D) ones, based on human neurons derived from induced pluripotent stem cells. To address the dynamic changes of the tissue microenvironment, bioreactors are used to control the in vitro microenvironment for viability, repeatability, and standardization. However, in neuronal tissue engineering, bioreactors have primarily been used for cell expansion purposes, while microfluidic systems have mainly been employed for culturing organoids. In this study, we explored the use of a commercial perfusion bioreactor to control the culture microenvironment of neuronal cells in both 2D and 3D cultures. Namely, neurons differentiated from human induced pluripotent stem cells (iNeurons) were cultured in 2D under different constant flow rates for 72 h. The impact of different flow rates on early-stage neuronal development and synaptogenesis was assessed by morphometric characterization and synaptic analysis. Based on these results, two involving variable flow rates were developed and applied again in 2D culture. The most effective protocol, in terms of positive impact on neuronal development, was then used for a preliminary study on the application of dynamic culturing conditions to neuronal cells in 3D. To this purpose, both iNeurons, co-cultured with astrocytes, and the human neuroblastoma cells SH-SY5Y were embedded into a hydrogel and maintained under perfusion for up to 28 days. A qualitative evaluation by immunocytochemistry and confocal microscopy was carried out to assess cell morphology and the formation of a 3D neuronal network.